Encyclopaedia Britannica 10-Minute Guide : Space. - Encyclopaedia Britannica, Inc. (Morton Grove, IL : Publications International, Ltd., 2017)
Concise overview of the major subjects of astronomy, from the origins of the galaxies, stars, and planets, to the major figures and milestones of the field.--
Keywords: Astronomy -- Miscellanea -- Juvenile literature; Outer space -- Juvenile literature; Juvenile works; Miscellanea